2000
DOI: 10.1136/bmj.320.7251.1708
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age and fetal loss: population based register linkage study

Abstract: Objective To estimate the association between maternal age and fetal death (spontaneous abortion, ectopic pregnancy, stillbirth), taking into account a woman's reproductive history. Design Prospective register linkage study. Subjects All women with a reproductive outcome (live birth, stillbirth, spontaneous abortion leading to admission to hospital, induced abortion, ectopic pregnancy, or hydatidiform mole) in Denmark from 1978 to 1992; a total of 634 272 women and 1 221 546 pregnancy outcomes. Main outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

73
837
28
66

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,412 publications
(1,004 citation statements)
references
References 16 publications
73
837
28
66
Order By: Relevance
“…It is reported that genetic abnormalities, uterine anatomical defects, antiphospholipid antibodies, environmental factors, advanced maternal age, obesity, endometriosis, etc. may be the possible causes of miscarriage in natural and assisted conceptions [20][21][22][23][24]. In our study, the higher miscarriage rates in patients over 35 years old may mainly result from advanced maternal age and aneuploid embryo since most of the other reasons were excluded before IVF cycle starting.…”
Section: Discussionmentioning
confidence: 67%
“…It is reported that genetic abnormalities, uterine anatomical defects, antiphospholipid antibodies, environmental factors, advanced maternal age, obesity, endometriosis, etc. may be the possible causes of miscarriage in natural and assisted conceptions [20][21][22][23][24]. In our study, the higher miscarriage rates in patients over 35 years old may mainly result from advanced maternal age and aneuploid embryo since most of the other reasons were excluded before IVF cycle starting.…”
Section: Discussionmentioning
confidence: 67%
“…Application of a fetal life-table approach to the data has, however, estimated the cumulative risk of fetal loss from the beginning of week 6 to be 11% (28), which matches national estimates of fetal loss (29). We did not have data to examine whether non-participation differed between women with limited workload and a miscarriage and women with heavy workload and a miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…RPL is a major concern in gynecology, affecting about 1-5 % of couples [2,4,5] and frequently accompanied by maternal morbidity as well as a considerable psychological burden. The risk of recurrence increases with the maternal age and number of successive losses [6,7]. It is a multifactorial disorder caused very often by genetic abnormalities (gene mutations and abnormal embryonic karyotypes), endocrine disorders, uterine anatomy anomalies, infectious or immunologic factors, alcohol use and chemical exposure [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%